Investigation of some commercial TLD chips/discs as UV dosimeters - Noh, A.M.; Amin, Y.M.; Mahat, R.H.; Bradley, D.A. (Elsevier, 2001)
Using a deuterium UV source, we have investigated the response of a number of commercially available thermoluminescence (TL) dosimeters (TLDs) to UV radiation (UVR), including LiF : Mg, Cu, P (TLD-100 H), CaF2 : Dy (TLD-200), CaF2 : Mn (TLD-400), Al2O3 (TLD-500), 7LiF : Mg, Cu, P (TLD-700 H) and CaSO4 : Dy (TLD-900). The intrinsic method was used to detect UVR, while trap depth and frequency factors were estimated using the initial rise method. We have studied TL intensity as a function of exposure time, observing high sensitivity of TLD-500 to UVR. Conversely, TLD-400 displays weak sensitivity to these same radiations. Although TLD-900 and TLD-200 are both less sensitive to UVR than TLD-500, they each provide a linear response to UVR. The possible use of these phosphors as UV dosimeters has been further appraised, examining thermal fading effects and fading due to light exposure.